KONSEPSI MASYARAKAT ACEH TERHADAP PANTI JOMPO - irma Juraida; Triyanto Triyanto; Rahma Husna Yana (Prodi Sosiologi FISIP Universitas Teuku Umar, 2019)
The nursing home as a social institution is a place of assistance for the elderly who are displaced and have socio-economic problems both in their families and communities. Even so, the existence of nursing homes in the community is still often seen as a bit sad and deemed incompatible with the teachings of religion and customs understood by most of the people of Aceh. This study aims to determine and analyze the community's conception of nursing homes as social institutions and use the theory of herbert mead interaction through a series of stages (mind, self and society). The method used in this study is a qualitative approach. The results of the field research show that the community (social) conception of nursing homes is determined more by the knowledge and understanding of informants representing the community in accordance with the values and norms that develop in the community concerned through a series of stages (mind, self and society).